Microteoria para cuidados de enfermagem na prevenção do delirium em pessoas idosas na UTI - Kinalski, Sandra da Silva (2022)
In intensive care units, elderly people are exposed to noise, social isolation, physical restriction, sleep deprivation, invasive devices, often triggering a disorder called delirium. It is an organic brain syndrome, with acute manifestation and simultaneous presence of disturbances in consciousness, attention, perception, thinking, memory, psychomotor behavior, emotions, sleep-wake rhythm, disorientation and disturbances in language, with a prevalence of up to 70% of the patients analyzed in the ICU. Theoretical models and nursing theories, by supporting care practices, can contribute to the improvement of theoretical and practical skills in nursing care, including the prevention of delirium in elderly people in the ICU. For the foundation of nursing care, Roy's Adaptation Model recognized the possibility of envisioning the integration of theory with clinical practice for the prevention of delirium in elderly people in the ICU. The research question that guided this study was: what theoretical relationships can be established between Roy's Adaptation Model and nursing care in the prevention of delirium in elderly people in the ICU through a nursing microtheory? And as a general objective: to develop a microtheory, of the prescriptive type, for nursing care in the prevention of delirium in elderly people in the ICU, supported by constructs of the Adaptation Model of Callista Roy. A basic, theoretical, prescriptive research was carried out, with a methodological structure based on the theoretical substruction process. Roy's Adaptation Model allowed the development of the theory's deductive path. In order to understand the phenomenon of nursing care in the prevention of delirium in elderly people in the ICU, an integrative literature review was carried out, as a method of synthesis, which contributed to the inductive path of the theory. The stages of conceptualization and operationalization of the microtheory were carried out. In the theoretical system, Roy's focal stimulus and contextual stimulus constructs were used. Thus, the concepts of focal care and contextual care were produced and from these subsumed, the adaptive response to prevention, being considered a variable. In establishing the relational statements of the theoretical system, four axioms, two postulates, eight propositions and an epistemic assumption were elaborated. Two empirical indicators were established in the operating system: the Confusion Assessment Method for Intensive Care Units and the demographic/clinical history of the elderly (alcoholism, smoking, previous cognitive impairment and dementia). In establishing the relational statements of the operating system, two transformational statements and four hypotheses were produced. A flowchart and a protocol were created for the practical implementation of the microtheory and to guide its use in the stages of the nursing process. This thesis contributes in an original way by defining nursing care in the prevention of delirium in the elderly through a construct of interest to nursing, in the organization of professional care actions in the Intensive Care Unit.